2014
DOI: 10.1186/1471-2164-15-941
|View full text |Cite
|
Sign up to set email alerts
|

Human placental transcriptome shows sexually dimorphic gene expression and responsiveness to maternal dietary n-3 long-chain polyunsaturated fatty acid intervention during pregnancy

Abstract: BackgroundPreviously we have examined the effect of maternal dietary n-3 long-chain polyunsaturated fatty acid (LCPUFA) supplementation during pregnancy on offspring fat mass. Considering the involvement of the placenta in fetal programming, we aimed to analyze the sex-specific gene expression in human term placenta and its response to the n-3 LCPUFA intervention, as well as their correlations to offspring adiposity.ResultsPlacental gene expression was assessed in a control and n-3 LCPUFA intervention group by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
63
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 82 publications
5
63
0
Order By: Relevance
“…It is plausible that the differential expression of placental genes by sex and diet accounts for the association. [40][41][42][43][44] Interestingly, the sex ratio of women with PAH versus non-PAH was equal in the study (data not shown). The exact mechanism through which fetal sex modifies dietary effects on PAH remains unclear.…”
Section: Discussionmentioning
confidence: 74%
“…It is plausible that the differential expression of placental genes by sex and diet accounts for the association. [40][41][42][43][44] Interestingly, the sex ratio of women with PAH versus non-PAH was equal in the study (data not shown). The exact mechanism through which fetal sex modifies dietary effects on PAH remains unclear.…”
Section: Discussionmentioning
confidence: 74%
“…In murine models obesity alters placental morphology, cell proliferation and inflammation [44] and maternal diet alters placental gene expression [45] and epigenetic systems [46] in a sexually dimorphic manner. Maternal dietary n-3 polyunsaturated fatty acid administration gave sexually dimorphic changes in gene expression in placentas in mice [47] and in humans [41]. The underlying basis for these sexually dimorphic differences in gene expression in placenta remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Higher miRNA expression would reduce expression of downstream target genes in placentas from folate‐deficient women; this was confirmed for ZEB2, MYC, and CDK6 at the mRNA level. Placental CDK6 expression positively correlates with birthweight , implying reduced expression under low folate conditions would negatively affect fetal growth. Reduced MYC and unaltered TP53 expression in placentas from women with low folate status contrast with FGR pregnancies, where both are elevated .…”
Section: Discussionmentioning
confidence: 99%